Prediction of prokinetic agents in critically ill patients with feeding intolerance: a prospective observational clinical study - Lv, Guangxuan; Zhang, Tao; Wang, Luping; Fu, Xin; Wang, Yucong; Yao, Hua; Fang, Huang; Xia, Xiaoxiao; Yang, Jing; Wang, Bo; Zhang, Zhongwei; Jin, Xiaodong; et al. (Frontiers in Nutrition, 2023)
Background Prokinetic agents are currently considered the first-line therapy to improve gastric emptying when feeding intolerance occurred in critically ill adults. In this study, we developed a technique to assess the feasibility of predicting prokinetic agent efficacy in critically ill patients. Methods The first images of each patient were obtained after EFI had occurred but before the first dose of prokinetic agents was administered and additional images were obtained every morning until the seventh day. The gastric antrum echodensity was recorded based on grayscale values (50th percentile, ED50; 85th percentile, ED85; mean, EDmean) and daily energy and protein intake was collected as the judgement for effective and ineffective group. A receiver operating characteristic curve was analyzed to distinguish the thresholds between the two groups and thus determine the ability of the gastric antrum echodensity to predict the efficacy of prokinetic agents. Results In total, 83 patients were analyzed. Patients in the ineffective group had a higher ED50 (58.13 ±14.48 vs. 49.88 ± 13.78, p < 0.001, difference 95%CI: 5.68,10.82), ED85 (74.81 ± 16.41vs. 65.70 ± 16.05, p < 0.001, difference 95%CI:6.16,12.05), and EDmean (60.18 ± 14.31 vs. 51.76 ± 14.08, p < 0.001, difference 95%CI :5.85,11.00) than those in the effective group. Patients in the effective group more easily reached the target energy 16.21 ± 7.98 kcal/kg vs 9.17 ± 6.43 kcal/kg (p < 0.001), 0.72 ± 0.38g/kg vs. 0.42 ± 0.31 g/kg (p < 0.001) than in the ineffective group intake by day. Conclusions The gastric antrum echodensity might serve as a tool for judging the efficacy of prokinetic agents, helping clinicians to decide whether to use prokinetic agents or place a post-pyloric tube when feeding intolerance occurs in critically ill patients